THE STUDY CORRELATION BETWEEN READING HABIT AND PRONUNCIATION ABILITY AT THE SECOND GRADE STUDENTS OF IKIP SILIWANGI - Aseptiana Parmawati (Eltin Journal : Journal of English Language Teaching in Indonesia, 2018)
Language has central role on intellectual development, social, and emotional students to supported success student and learn all of lessons. Literacy level are performation, functional, informational, and epistemic. Performative level means students able to read, to write, to listen, and to speak using symbols. Reading habit refers to the automatic process as the readers read the textual material and deriving meaning unconsciously. A good reading habit is important for the development of personalities and mental capacities. Students reading habit plays an important role in pronunciation mastery. This research used the correlation research. The objectives of the study is to reveal correlation between students’ reading habit and their pronunciation ability at second grade students of IKIP Siliwangi. The finding was supported by the result of students’ scores. The minimum score of habit is 71 and 65 for pronunciation ability. The maximum score of reading habit is 109 and 92 for pronunciation ability. The mean of reading habit is 92.60 and 78.73 for pronunciation ability. Standard deviation of reading habit is 8.85 and 6.31 for pronunciation ability. The researcher finds that the Pearson Product Moment of both variable is 0.373. It means that the correlation between students’ reading habit in English and their pronunciation ability was in low correlation because in the range of 0.20-0.40. From the result of the statistical calculation, it can be synthesized that Null Hypothesis (Ho) is rejected. The researcher concluded that there is the correlation between students’ reading habit and their pronunciation ability. Keywords: Reading habit, Pronunciation, Correlation